(3eWdY GdHOhQ heLeY GdHMhQs - (3Gdjefj, , Uaj GdOjf, CMeO Hf UGdM Hf CHj GdQLGd, (B1092 (3g`s
(3ChdgG (B:s
(3MQa GdZjf GdeYLeI ; ZGdH Hf YKeGf GdgeOGfj GdeTGYQj GdHGYWj (B- (3QMeg Gddg (B- (3ef Yjhf GdTjYI hNjGQge hdYd fSHJg Edi Pj GdeTYGQ GdhGaO Ydi QShd Gddg Udi Gddg Ydjg hSde (B...s
(3BNQgG (B:s
... (3GdYdGeI jhSa GdfYeGf ef eYGUQj GdEeGe UdGM Hf Ydj Ydjg GdSdGe GfJgis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B1\137s
(3EjVGM Gdecfhf (B2\500s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJGQjNs